The determination of alpha naphthyl acetate esterase (anae) positivity in peripheral blood leukocytes of kyrgyzstan?s mountain yaks (bos grinniens) - Nariste Kadıralieva; Emrah Sur; Yasemin Öznurlu; Tuğba Özaydın (Eurasian Journal of Veterinary Sciences)
Aim: A lysosomal enzyme, alpha naphthyl acetate esterase (ANAE), has been used to differentiate T and B lymphocytes, and monocytes in various species in peripheral blood smears. In this study, it was aimed to determine the positivity of the ANAE in peripheral blood leukocytes of Kyrgyzstan's mountain yaks, as also known Topoz, (Bos grinniens). Materials and Methods: As a material, the peripheral blood samples collected from healthy thirteen Kyrgyzstan's mountain yaks, 2?4 year old aged, were used. ANAE was demonstrated on smears prepared from blood samples. Results: ANAE-positivity was observed in all monocytes and only some lymphocytes. ANAE-positivity pattern in lymphocytes was dot like characterized with 1-4 reddish-brown cytoplasmic granules while all monocytes have a diffuse, fine granular enzymatic reaction along whole cytoplasm. No enzymatic reaction was observed in neutrophil and eosinophil leukocytes. The ANAE positive lymphocyte rate was found to be 58,85 % in Kyrgyzstan's mountain yaks. Conclusion: Studies on Kyrgyzstan mountain yaks have been extremely limited due to their living conditions and aggressive temperaments of these animals. Therefore, any kind of structural, histological, enzyme histochemical, physiological, biochemical and anatomical studies on these animals, as well as case reports of various diseases that may be faced by veterinary clinicians or academicians working in the country, will guide the studies to be carried out on these animals in future.